Decolonizing the Malaysian Mind: Celebrating the Pioneering Achievement of Lloyd Fernando’s Cultural Politics - Lim, Shirley Geok-Lin (SARE: Southeast Asian Review of English, 2018)
This article maps Lloyd Fernando’s contributions to Malaysian English-language literature as Head of English at the University of Malaya, examines his negotiations with the inception of Bahasa Malaysia (Malay) as National Language and the downgrading of Malaysian English writing to sectional literature recorded in Cultures in Conflict (1986) and concludes with comparative readings of this collection and his novel, Scorpion Orchid (1976).